Women and Discourse in the Fiction of Marguerite Duras - Cohen, Susan D. author. aut Link
IX, 239 p.
Keywords: The first comprehensive study of the narrative and stylistic characteristics of all of Marguerite Duras' major works. Through close textual readings with a particular focus on women's access to language, this book shows how Duras critiques and subverts dominant discourse. Duras' textual strategies are described within a discussion of narrativity which also addresses factors of race and class. Cohen demonstrates how Duras achieves the famous ritual atmosphere of her prose through precise techniques which connect to her critique of representation.